Oncology Medical Home: ASCO and COA Standards. Issue 8 (August 2021) - Woofter, Kim; Kennedy, Erin B.; Adelson, Kerin; Bowman, Ronda; Brodie, Rachel; Dickson, Natalie; Gerber, Rose; Fields, Karen K.; Murtaugh, Carol; Polite, Blase; Paschall, Marcus; Skelton, Matthew; et al.
Abstract : PURPOSE: To provide Standards on the basis of evidence and expert consensus for a pilot of the Oncology Medical Home (OMH) certification program. The OMH model is a system of care delivery that features coordinated, efficient, accessible, and evidence-based care and includes a process for measurement of outcomes to facilitate continuous quality improvement. The OMH pilot is intended to inform further refinement of Standards for OMH model implementation. METHODS: An Expert Panel was formed, and a systematic review of the literature on the topics of OMH, clinical pathways, and survivorship care plans was performed using PubMed and Google Scholar. Using this evidence base and an informal consensus process, the Expert Panel developed a set of OMH Standards. Public comments were solicited and considered in preparation of the final manuscript. RESULTS: Three comparative peer-reviewed studies of OMH met the inclusion criteria. In addition, the results from 16 studies of clinical pathways and one systematic review of survivorship care plans informed the evidence review. Limitations of the evidence base included the small number of studies of OMH and lack of longer-term outcomes data. More data were available to inform the specific Standards for pathways and survivorship care; however, outcomes were mixed for the latter intervention. The Expert Panel concluded that in the future, practices should be encouraged to publish the results of OMH interventions in peer-reviewed journals to improve the evidence base. STANDARDS: Standards are provided for OMH in the areas of patient engagement, availability and access to care, evidence-based medicine, equitable and comprehensive team-based care, quality improvement, goals of care, palliative and end-of-life care discussions, and chemotherapy safety. Additional information, including a Standards implementation manual, is available at www.asco.org/standards .